2021
DOI: 10.1021/acs.jafc.1c03398
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Off-Flavors of Plant-Based Proteins

Abstract: Proteins and, in particular, plant-based proteins are becoming more and more important in the face of future challenges, resulting from continuous population growth, the imbalance between malnutrition and overweight/obesity, and environmental changes. Recent developments open new avenues for improving the quality and sustainable production of plant proteins. Increasing knowledge on the key drivers of the off-flavor of plant proteins, which currently limit their use, supports new strategies to reach full flavor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 30 publications
1
48
0
Order By: Relevance
“…However, various off-flavor-producing compounds, including hexanal, heptanal, 2-octenal, 1-octen-3-ol, and benzaldehyde, were detected and linked to an unpleasant beany and grassy odor in the proteins isolated from these beans. It is known that most bean proteins used for producing plant-based meat analogs release the same off-flavors [ 30 , 34 ]. These compounds affect the overall flavor of the final product [ 32 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, various off-flavor-producing compounds, including hexanal, heptanal, 2-octenal, 1-octen-3-ol, and benzaldehyde, were detected and linked to an unpleasant beany and grassy odor in the proteins isolated from these beans. It is known that most bean proteins used for producing plant-based meat analogs release the same off-flavors [ 30 , 34 ]. These compounds affect the overall flavor of the final product [ 32 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that most bean proteins used for producing plant-based meat analogs release the same off-flavors [ 30 , 34 ]. These compounds affect the overall flavor of the final product [ 32 , 34 ]. This phenomenon limits the consumer acceptability of the products [ 1 , 8 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main ingredient of PBA3 was pea protein concentrate and it was not significantly different from the other PBAs in terms of texture or overall liking, but it did score the lowest for the participants’ liking of flavor. Pea protein has been associated with bitterness, beany, earthy, and astringency [ 39 , 40 ], which may have led to the participants’ disliking of the flavor of PBA3.…”
Section: Resultsmentioning
confidence: 99%
“…PBA3, containing pea protein concentrate, was separated from all other samples and was associated with fatty, nutty, off-flavor, fibrous, and chewy. Past studies have found that pea protein can lead to off-flavors [ 39 ] and chewiness in meat analogs [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another challenge is simulating the taste and aroma of meat products due to the extreme complexity of the compounds associated with the flavor of meat (He et al., 2020; Li & Li, 2020). Furthermore, off‐flavors, such as a beany flavor, a bitter taste, an aftertaste, and astringency, are often detected in plant‐based alternatives (Mittermeier‐Kleßinger et al., 2021; Sha & Xiong, 2020). “Off‐flavors” refer to objectionable flavors, including perceived undesirable tastes, odors, and other sensations such as astringency.…”
Section: Introductionmentioning
confidence: 99%